(untitled) (Solukhumbu Multiple Campus Research Journal, 2025)
Indirect Technique refers to methods of estimating demographic measures such as fertility, mortality, and migration. The title of this study is the evaluation and need for indirect techniques for demographic estimation. The objectives of this study are to explore the descriptive analysis of indirect techniques and their concept, historical development, and contemporary necessity in demographic research. This study is based on secondary sources of data, including academic notes, textbooks, and scholarly articles. These findings demonstrated the importance of both direct and indirect methods of demographic estimation. Some examples of direct estimation include censuses, vital registration system, and surveys. The study explores both direct and indirect demographic techniques are essential for estimating demographic data and correcting demographic errors. Direct techniques of population estimation, includes the collection of population data through censuses, vital registration system, and sample surveys. However, indirect technique indicates this demographic estimation which is relatively straight forward to apply and produce more accurate demographic data by detecting inconsistencies and adjusting imperfect data. Both direct and indirect techniques of demographic estimation are essential for generating accurate and reliable demographic data and information, monitoring population changes over time, and supporting evidence-based policy formulation and development planning. Furthermore, indirect techniques or estimation developed across various countries enhance the comparability and validity of demographic analysis in data-deficient settings. So, indirect techniques play a central role in improving the quality of demographic data and are indispensable tools for demographers and policymakers working in contexts where direct demographic data are limited.